7. How Professional Musicians Can Better Connect to Audiences for Live Classical Music: Assessing Theory And Practice in the Light of the COVID-19 Crisis - John Sloboda (Psychological Perspectives on Musical Experiences and Skills: Research in the Western Balkans and Western Europe, 2024)
This chapter aims to increase understanding of how artists and promoters can respond to audience needs through practical but theoretically grounded adjustments to the concert experience. It does this by drawing out key elements of an artist-led series of research projects which brought musicians and researchers together to explore how more of what audiences seek can be added to live classical events through principled innovations in programme design, content, and presentation. These projects drew on a framework provided by Sloboda and Ford (2019), which identifies four key dimensions on which concerts can vary. Four case studies are discussed, each focusing primarily on one of the four dimensions in the framework, with summary accounts of methodology, findings, and implications. The chapter concludes with a consideration of how these understandings might be adapted and enlarged to reflect the experiences, challenges, and opportunities faced by musicians giving concerts during the Covid-19 restrictions of 2020.